1986
DOI: 10.2307/1541623
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Mucous Trails by Intertidal Limpets to Enhance Food Resources

Abstract: The mucous trails secreted by certain species of intertidal limpets serve as adhesive traps for the microalgae that are their primary food resources. The mucous trails of two solitary homing limpets, Lottia gigantea and Collisella scabra, also stimulate the growth of microalgae. In contrast, the mucous trails of an aggregating limpet, Collisella digitalis, and the carnivorous dog whelk, Nucella emarginata, do not stimulate microalgal growth. These results may be explained by differences in the behavior of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
58
0
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 29 publications
5
58
0
1
Order By: Relevance
“…In the control chamber attached and free-living bacterial biomass reached only about 10 and 15% of the bacterial biomass of the chambers containing mucuscoated coverslips. Mean TCHO content of freshly secreted pedal mucus of M. turbinata was 96.85 pg TCHO mg-l (mucus dry wt)(SD= 11.63, n= 12) or 9.7% of the dry wt; Connor (1986) found TCHO contents ranging from 8.1 to 18.4% of mucus dry weight in limpets, with higher TCHO fractions in homing limpets.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…In the control chamber attached and free-living bacterial biomass reached only about 10 and 15% of the bacterial biomass of the chambers containing mucuscoated coverslips. Mean TCHO content of freshly secreted pedal mucus of M. turbinata was 96.85 pg TCHO mg-l (mucus dry wt)(SD= 11.63, n= 12) or 9.7% of the dry wt; Connor (1986) found TCHO contents ranging from 8.1 to 18.4% of mucus dry weight in limpets, with higher TCHO fractions in homing limpets.…”
mentioning
confidence: 82%
“…Only about 25% of the mucus-derived carbohydrates remained on the substrate after 26 h. ductivity (Ducklow in press). Since mucus consists primarily of polysaccharides and proteins with C: N ratios of l-5 (Connor 1986), we hypothesized that mucus trails produced by marine invertebrates are readily degradable by microbes (see also Calow 1979) and are able to support significant microbial growth. To test this hypothesis, we investigated the course of microbial colonization and decomposition of mucus trails produced by the nearshore herbivorous gastropod species Monodonta turbinata in the Adriatic Sea.…”
mentioning
confidence: 99%
“…Gastropods produce trails of mucus as they crawl, spending up to 80 % of assimilated energy in this process (Edwards & Welsh 1982, Horn 1986, Davies et al 1991. Gastropod pedal mucus consists primarily of proteins and polysaccharides with low C : N ratios (Connor 1986). In a previous study (Herndl & Peduzzi 1989) it could be shown that mucous trails produced by marine gastropods are readily degradable and rapidly utilized by microheterotrophs.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on marine mucus secretion found that roughly 50% of the dry weight was inorganic residue (Connor, 1986;Davies et al, 1990). This value can also be estimated from the percentage of inorganic salts in seawater (3.56%) (Schmidt-Nielsen 1990); for typical marine mucus containing 96 -98% water, we would predict that inorganic material would make up 46 -64% of the dry weight (Sallam et al, 2009).…”
Section: Data Inmentioning
confidence: 81%